(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study determined the effects of sleep deprivation on the academic performance of 2nd-year education students of the University of Science and Technology of Southern Philippines. Specifically, it sought to answer the following: (1) correlation and comparison of difference between number of hours sleep and academic performances in Eng111 and Educ90; (2) difference on students’ flexibility towards sleep deprivation and demographic profile; and (3) correlation between the number of hours sleep and academic performances in terms of Cognitive, Psychomotor/Physical, and Environmental Factors Correlational-descriptive research design was used in the study. A census was used in the collection of data in which 122 respondents participated. A researcher-made questionnaire was utilized. The analytical design used consisted of statistical procedures such as hypothesis testing, correlation, averages, standard deviations, and T-test. The results showed that as the number of hours of sleep increased, students’ academic performance in Eng111 and Educ 90 get better. Furthermore, a significant difference in both subjects and grades was found. With all the variables taken in this study, it can be inferred that without proper sleep, the brain’s function such as the ability to concentrate, store data, and other cognitive activities will be hampered and/or paralyzed..